Classical and quantum analysis of an Einstein-Scalar solution in 2+1 dimensions - Gurtug, O.; Mazharimousavi, S. Habib; Halilsoy, M. (Springer Heidelberg, 2017)
The classical and quantum properties of a new solution obtained in (2+1)-dimensional gravity coupled with a real scalar field is analyzed in detail. The considered new solution is a one-parameter generalization of a previously known solution. We investigate the solution classically by calculating exact null and null circular geodesics which correspond to a typical particle probe of the correspondsing black hole spacetime. The solution admitting naked singularity is investigated within the context of quantum mechanics. The timelike naked singularity is probed with spin-zero and spin-half quantum particles. We show that the curvature singularity in the new solution is stronger and hence in general the spacetime remains quantum singular with respect to a quantum particle probe.
Keywords: (2+1)-Dimensional Black-Hole; Spacetime; Singularities; Gravity; Fields